Gramaticalização e tradição discursiva: um estudo dos processos constitutivos do texto relacionados a assim - Lopes-Damasio, Lúcia Regiane [UNESP] (My University, 2010)
This paper is focused in a qualitative analysis on the item assim in correlation to its topic function in Tradições Discursivas (Discursive Traditions), investigated in the from 18th to 21th centuries. The results point out to a close relation between the investigated texts traditions and the changes that have occured concerning the item mentioned above, from a historical conception of non-linear diachrony.

Associação Portuguesa de Linguística - Porto, Portugal (org.) Ana Maria Brito, depósito legal n. 170.391/01
Keywords: Grammaticalization; Discursive traditions; assim; Análise Lingüística; Tradição discursiva; Mudança linguística; Gramaticalização; Tradição discursiva; Assim